2020
DOI: 10.1007/s11096-020-01147-5
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors, and outcomes of acute kidney injury in the intensive care unit in Sudan

Abstract: Background There is a paucity of studies in acute kidney injury in the intensive care unit, particularly in Sudan. Objectives The current study has estimated the incidence; risk factors and outcomes of subjects with acute kidney injury developed during admission to the intensive care unit at Fedail Hospital, Khartoum, Sudan. Methodology This was a cross-sectional study conducted in the intensive care unit during the period from July 2018 to June 2019. The data was collected from the clinical profiles of all ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 32 publications
4
18
1
Order By: Relevance
“…Similar figures have been found in studies of other countries such as Burundi (17.4%) [ 15 ], Côte d'Ivoire (26.2%) [ 16 ], Burkina Faso (24%) [ 17 ], Nigeria (28.8%) [ 18 ], Ethiopia (29.1%) [ 19 ], and South Africa (31%) [ 20 ]. On the other hand, higher rates than ours were reported in Egypt (30% to 60%) [ 21 ], the United States (39%) [ 22 ], Japan (62%) [ 23 ], and Sudan (91%) [ 24 ]. This difference can be explained by a number of factors, including the sociodemographic characteristics of the study population.…”
Section: Discussioncontrasting
confidence: 59%
“…Similar figures have been found in studies of other countries such as Burundi (17.4%) [ 15 ], Côte d'Ivoire (26.2%) [ 16 ], Burkina Faso (24%) [ 17 ], Nigeria (28.8%) [ 18 ], Ethiopia (29.1%) [ 19 ], and South Africa (31%) [ 20 ]. On the other hand, higher rates than ours were reported in Egypt (30% to 60%) [ 21 ], the United States (39%) [ 22 ], Japan (62%) [ 23 ], and Sudan (91%) [ 24 ]. This difference can be explained by a number of factors, including the sociodemographic characteristics of the study population.…”
Section: Discussioncontrasting
confidence: 59%
“…After logistic regression, a Zimbabwean study found that the odds of developing AKI were 3.3 for elevated blood pressure and 6.0 for CKD [ 32 ]. In a Sudanese cohort, cardiovascular disease (adjusted odds ratio (AOR) = 3.4; 95% Confidence Intervals (95% CI): 1.2–9.4), diabetes mellitus (AOR = 2.6; 95% CI: 1.2–6.0) and hypertension (AOR = 2.4; 95% CI: 1.2–5.4) were significant predictors of the development of AKI [ 44 ].…”
Section: Factors Associated With Aki In Sub-saharan Africamentioning
confidence: 99%
“…As in developed countries, the major risk factors for AKI in SSA are comorbidities such as diabetes mellitus, hypertension, cardiovascular disease, and obesity, which are a corollary of the progressive westernisation of SSA society [32][33][34][44][45][46]. As Olowu et al point out, the rapid urbanisation of SSA combined with an increase in the prevalence of these noninfectious comorbidities have significantly influenced the clinical features of AKI [8].…”
Section: Preexisting Conditions (Comorbidities)mentioning
confidence: 99%
“…Acute kidney injury (AKI) commonly takes place in critically ill patients, especially in those of adult intensive care unit (ICU) patients. With the integration of consensus AKI definition criteria from Risk, Injury, Failure, Loss, End-Stage Kidney Disease (RIFLE), Acute Kidney Injury Network (AKIN), and the recent Kidney Disease Improving Global Outcomes (KDIGO), incidence of AKI in adult ICU has been estimated to be around for 16-67% [1][2][3][4][5][6][7][8][9][10][11]. Clinically observational studies have even more shown that in a large 10-year cohort study that enrolled more than 90,000 patients from more than 20 ICUs, AKI incidence increased by 2.8% per year [3], highlighting that this disease entity is in the increasing process worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental causes of AKI have been keenly surveyed from many perspectives [4][5][6][7][8][9][10][11][12][13][14][15], including toxic substances such as chemical compounds and medicines, sepsis syndrome (SS)-associated ischemic kidney injury and acute ischemia-reperfusion (IR) injury, contrast medium, obstruction of the urinary tract, chronic advanced heart failure, hepato-renal syndrome, hypoperfusion/shock, etc. Additionally, acute kidney IR injury has been clearly identified as one of the crucial contributors of AKI [4,5,11,16], and majority of the causal etiologies of AKI can also contribute to acute IR injury in kidney [2,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%